2002
DOI: 10.1093/alcalc/37.2.169
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF ACUTE ALCOHOL INTOXICATION ON PITUITARY-GONADAL AXIS HORMONES, PITUITARY-ADRENAL AXIS HORMONES, beta-ENDORPHIN AND PROLACTIN IN HUMAN ADULTS OF BOTH SEXES

Abstract: - The effects of acute alcohol intoxication (AAI) on the pituitary-gonadal axis hormones, and the possible contribution of pituitary-adrenal axis hormones, beta-endorphin and prolactin to alcohol-induced dysfunction of pituitary-gonadal axis hormones were studied in adult men and women. Blood samples were drawn from adults of both sexes who arrived at the emergency department with evident behavioural symptoms of drunkenness (AAI) or from adult volunteers with nil consumption of alcohol (controls). Our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 27 publications
5
60
0
Order By: Relevance
“…While Frias et al (2000) reported that alcohol ingestion produced a decrease in plasma testosterone levels and no significant changes in either FSH or LH levels; Little et al (1992) demonstrated that administration of alcohol to prepubescent males stimulated testosterone secretion with no changes in serum LH. Furthermore, they stated that when alcohol was administered to adult male rats, both testosterone and LH levels decreased.…”
Section: Discussionmentioning
confidence: 99%
“…While Frias et al (2000) reported that alcohol ingestion produced a decrease in plasma testosterone levels and no significant changes in either FSH or LH levels; Little et al (1992) demonstrated that administration of alcohol to prepubescent males stimulated testosterone secretion with no changes in serum LH. Furthermore, they stated that when alcohol was administered to adult male rats, both testosterone and LH levels decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Since the ovary is an important source of circulating progesterone and allopregnanolone in humans (Rapkin et al, 1997;Genazzani et al, 2002), the study included women in follicular (AAI, n ¼ 10; controls, n ¼ 7) or luteal (AAI, n ¼ 10; controls, n ¼ 8) phases of their ovarian cycle. Their consumption of alcohol was confirmed by the measurement of blood alcohol concentrations, using a gas-chromatographic head-space method described previously by our group (Frias et al, 2002). Statistically significant differences between the groups were analyzed by a two-way ANOVA.…”
Section: Methodsmentioning
confidence: 99%
“…Ethanol and its metabolite acetaldehyde have a direct toxic effect on Leydig cells but, on the other hand, there is a disruption on the hypothalamic-pituitary-gonadal axis. Chronic alcohol exposure decreases circulating LH levels and the response of LH to GnRH is reduced in alcoholics [5]. Disturbance of the hypothalamic-pituitary-gonadal axis persists over months of abstinence, with sustained increases in serum free and total testosterone levels in the presence of inadequate raised LH concentrations [2].…”
Section: Discussionmentioning
confidence: 99%